Interdisciplinary STEM education: Exploring technology and engineering integration in mathematics and science classes - Özacar, Başak Helvacı (My University, 2018)
STEM education is one of the trend topics in education in many countries, especially in Turkey. One of the biggest concern in STEM Education is the efficient and meaningful use of technology and engineering. Qualified and tech-savvy teachers are needed for the area as a result of the pedagogy of STEM Education and the interconnectedness of these disciplines. New research and professional development programs are required to be conducted when such post-modern paradigms raise because teachers are being asked to become proficient at new skills and responsibilities and implement these into their practices. This study investigates how STEM teachers implement and integrate technology and engineering, which tools do they use more frequently as a part of their science and mathematics lessons in 5th and 6th-grade topics. The ulterior motive of the study is to explore the effect of integrating technology and engineering in the overall quality of STEM lesson plans. The data obtained from 32 science and mathematics teachers who participated in TÜSİAD STEM Project: a teacher professional development program. The teachers attended four face-to-face STEM workshops, each received one STEM kit with a guide including six STEM lesson plans. During this professional development program, at least one lesson plan was implemented by participant teachers and they gathered together to reflect on their classroom experiences. At the end of the professional development program, teachers created their own authentic lesson plans. These lesson plans were investigated in terms of interdisciplinarity -integrating technology and engineering into science and mathematics classes. Overall, findings demonstrated that the science and mathematics teachers in the professional development program integrates technology and engineering in six different categories. Although, there is no significant difference reported on integrating technology on the quality of STEM lesson plans, engineering integration showed a significant difference in the quality of STEM lesson plans.

STEM eğitimi özellikle Türkiye olmak üzere birçok ülkede popülerdir. STEM eğitimindeki en büyük kaygılardan biri teknoloji ve mühendisliğin etkili ve anlamlı şekilde kullanımıdır. Nitelikli ve teknolojiyi yakından takip eden öğretmenlere olan ihtiyaç; STEM eğitiminin pedagojisi ve STEM alanlarının birbirleri ile bağlantıları sonucu ortaya çıkmıştır. Hızla değişen dünya ve post modern paradigmalar; öğretmenlerin yeni beceriler kazanmalarını gerektirir ve onlara yeni sorumluluklar yüklerken; yeni araştırmaların yapılması ve öğretmen mesleki gelişim programlarının düzenlenmesi bir gerekliliktir. Bu çalışmanın STEM öğretmenlerinin 5. ve 6. sınıf fen bilimleri ve matematik derslerinde, teknoloji ve mühendisliği nasıl ve hangi araçlarla bütünleştirdiği ve uyguladığını araştırmaktadır. Çalışmanın bir diğer hedefi ise öğretmenlerin, teknoloji ve mühendislik disiplinlerini kendi disiplinleri ile bütünleştirmelerinin STEM ders planlarının genelindeki etkisini keşfetmektir. Araştırmada bir öğretmen mesleki gelişim programı olan TÜSİAD STEM Projesi’ne katılan 32 fen bilimleri ve matematik öğretmeninin STEM ders planları veri olarak kullanılmıştır. Programa katılan öğretmenler dört yüz yüze STEM çalıştayına katılmış, içinde 6 ders planının olduğu bir rehber ve bir STEM kiti almıştır. Bu mesleki gelişim programı süresince öğretmenler en az bir ders planını sınıflarında uygulamışlar ve deneyimlerini paylaşmak üzere bir araya gelmişlerdir. Programın sonunda öğretmenler kendi özgün ders planlarını hazırlamışlardır. Hazırlanan STEM ders planları disiplinlerarasılık ilkesi — teknoloji ve mühendislik disiplinlerinin matematik ve fen bilimleri disiplinleriyle bütünleştirilmesi çerçevesinde incelenmiştir. Sonuç olarak, bulgular öğretmen mesleki gelişim programına katılan fen bilimleri ve matematik öğretmenlerinin teknoloji ve mühendislik disiplinlerini altı farklı kategoride bütünleştirdiğini göstermektedir. Teknoloji disiplininin bütünleştirilmesi STEM ders planlarının genelinde anlamlı bir değişikliğe sebep olmazken, mühendislik disiplininin bütünleştirilmesinin istatistiki olarak anlamlı bir değişikliğe sebep olduğu saptanmıştır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Eğitim ve öğretim; Education and training; Eğitici eğitimi; Trainer training; Fen bilgisi eğitimi; Science education; Hizmet içi eğitim; In service training; Matematik eğitimi; Mathematics education